A grounded theory study on the dynamics of parental grief during the children's end of life. (1st March 2023) - Kochen, Eline M.; Grootenhuis, Martha A.; Teunissen, Saskia C. C. M.; Boelen, Paul A.; Tataranno, Maria‐Luisa; Fahner, Jurrianne C.; de Jonge, Roos R.; Houben, Michiel L.; Kars, Marijke C.; ,
Abstract: Aim: Parents are increasingly confronted with loss during their child's end of life. Healthcare professionals struggle with parental responses to loss. This study aimed to understand parental coping with grief during their child's end of life. Methods: A grounded theory study was performed, using semi‐structured interviews with parents during the child's end of life and recently bereaved parents. Data were collected in four children's university hospitals and paediatric homecare services between October 2020 and December 2021. A multidisciplinary team conducted the analysis. Results: In total, 38 parents of 22 children participated. Parents strived to sustain family life, to be a good parent and to ensure a full life for their child. Meanwhile parents' grief increased because of their hypervigilance towards signs of loss. Parents' coping with grief is characterised by an interplay of downregulating grief and connecting with grief, aimed at creating emotional space to be present and connect with their child. Parents connected with grief when it was forced upon them or when they momentarily allowed themselves to. Conclusion: The parents' ability to engage with grief becomes strained during the end of life. Healthcare professionals should support parents in their search for a balance that facilitates creating emotional space.